A pilot study investigating reactive oxygen species production in capillary blood after a marathon and the influence of an antioxidant-rich beetroot juice - Clifford, T.; Bowman, A.; Capper, T.; Allerton, D. M.; Foster, E.; Birch-Machin, M.; Lietz, G.; Howatson, G.; Stevenson, E. J. (Applied Physiology, Nutrition, and Metabolism, 2018)
We report that reactive oxygen species (ROS), as measured in capillary blood taken from the finger-tip, increased after a marathon (+128% P < 0.01; effect size = 1.17), indicating that this collection method might be useful for measuring ROS in field settings. However, mitochondrial DNA damage remained unchanged. Beetroot juice, taken before and after exercise, was unable to mitigate exercise-induced ROS production, questioning its use an antioxidant-rich food.